A experiência socialista soviética no ensino de história - Costa, Narendranath Martins (2018)
The research has as its central theme the history of the Soviet experience in PNLD textbooks. The same investigates if the way in which the authors present the Soviet history attend to the PCNs and if they can attend the current BNCC. In the first chapter, we approach the research on the didactic book of history in Brazil, trying to find the state of the art. In the second chapter we turn to the history of the USSR and its legacy to humanity. In the third chapter, we present a diagnosis in the schools analyzed, through questionnaires applied and we weave considerations, taking into account the hypotheses raised, for this research. In the fourth chapter we started to analyze some textbooks already used in state high schools that we work with. We also raised a critique of the general concept of totalitarianism, as well as questioning the use of historiography, which used Soviet primary sources, supposed totalitarianism in the 1921-1930 and 1931-1940 decades in the USSR. In the fifth chapter, we try to establish a little of the history of the BNCC, exposing it and comparing it with other legal institutes, linked to the content of history for high school, focusing on teaching about the Soviet socialist experience. In the sixth chapter we present the theoretical methodological focus of the textbooks analyzed and criticize these in light of the BNCC. This study concluded that the history textbooks, analyzed, did not meet the PCNs and can not even attend the BNCC. The textbooks continue to reproduce stereotypes and clichés about the USSR and worse, do not seem to account for the skills and abilities required by the laws already cited, especially about the Stalin period. Students continue to reproduce far more representations based on sources outside the school environment and common sense on themes such as socialism and history of the Soviet socialist experience. From this research, we elaborate a handbook that puts side by side with fragments of the narratives of the analyzed authors, other sources and we also establish our narrative, for the same events, which appears as a synthesis produced by the comparison between the fragments of the authors' discourses and discourses that refute or even raise doubts about the authors' statements about the history of the USSR.